2016
DOI: 10.1098/rspb.2016.1506
|View full text |Cite
|
Sign up to set email alerts
|

In situ developmental responses of tropical sea urchin larvae to ocean acidification conditions at naturally elevated p CO 2 vent sites

Abstract: Laboratory experiments suggest that calcifying developmental stages of marine invertebrates may be the most ocean acidification (OA)-sensitive life-history stage and represent a life-history bottleneck. To better extrapolate laboratory findings to future OA conditions, developmental responses in sea urchin embryos/larvae were compared under ecologically relevant in situ exposures on vent-elevated p CO 2 and ambient p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 59 publications
(136 reference statements)
2
23
0
Order By: Relevance
“…This was despite a low pH that is similar to that expected at the end of this century (Uthicke et al, ). By contrast, in situ Echinometra larval growth studies in these sites showed that exposure to future OA conditions can lead to stunted and abnormal growth (Lamare et al, ). This is in agreement with previous laboratory studies on the same genus (Uthicke, Soars, et al, ) and on a wide variety of sea urchins from tropical to arctic regions (Byrne et al, ).…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…This was despite a low pH that is similar to that expected at the end of this century (Uthicke et al, ). By contrast, in situ Echinometra larval growth studies in these sites showed that exposure to future OA conditions can lead to stunted and abnormal growth (Lamare et al, ). This is in agreement with previous laboratory studies on the same genus (Uthicke, Soars, et al, ) and on a wide variety of sea urchins from tropical to arctic regions (Byrne et al, ).…”
Section: Introductionsupporting
confidence: 93%
“…In fact, there are a number of studies that point to the potential for adaptation to reduced pH across a range of invertebrate taxa, for example, in bivalves (Zhao et al, ), crustaceans (Thor & Dupont, ) and echinoderms (Kelly, Padilla‐Gamiño, & Hofmann, ). Similarly, experimentation on taxa living in naturally occurring CO 2 vent communities can increase our understanding of the acclimation potential of species both within (Uthicke et al, ) and across generations (Lamare, Liddy, & Uthicke, ).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Specifically, genes central to energy metabolism and biomineralization are downregulated in larvae of L. variegatus and other sea urchins reared in a lower pH, reducing growth rates (O'Donnell et al 2010, Stumpp et al 2011, Raven et al 2005, Kroeker et al 2010), i.e., larvae have smaller total body and average rod lengths. In addition, decreased pH also causes an increase in asymmetry in L. variegatus and other sea urchin larvae (Byrne et al 2013a, Uthicke et al 2013, Lamare et al 2016. Under low pH, larvae allocate the few available calcium carbonate ions disproportionally between rods leading one rod to grow more than the other.…”
Section: Discussionmentioning
confidence: 99%